Factors Influencing the Intention for Early Retirement: A Case Study Among Teachers at Secondary Cluster Schools in Dungun, Terengganu - Adida Muhammud; Najdah Abd Aziz; Rubiah Abu Bakar; Shahariah Harun (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2022)
Purpose: Teachers' roles in delivering classroom instructions and executing lessons in this 21st century is much bigger than assumed by many who are not in the teaching field. Some people perceived teaching is a stressful job and those who do not have the passion would give up after a certain number of years. Many have opted for early retirement and this number has increased year by year. Thus, this study aims to analyze the factors (health, school management and workload) that influence teachers' intention towards early retirement. Design/Methodology/Approach: 152 teachers were chosen from four cluster schools in Dungun, Terengganu and online questionnaires were distributed among them using Stratified Random Sampling Method. The data was analyzed using SPSS. Findings: The results show only teachers' health influence them towards early retirement intention. Meanwhile, the other factors are viewed as a challenge in the teaching world and would not influence them to opt for early retirement. Implications/Originality/Value: This finding will assist the Ministry of Education in taking actions, to circumvent   teachers from leaving their profession before reaching the compulsory retirement age. As a result, the school's management will focus on improved alternatives in managing the teachers' welfare and controlling the factors of early retirement among teachers.